2014
DOI: 10.1186/1472-6831-14-46
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about tooth avulsion and its management among dental assistants in Riyadh, Saudi Arabia

Abstract: BackgroundStudies evaluating dental assistants’ knowledge about tooth avulsion and its management are rare. The purpose of this study was to evaluate the level of knowledge about tooth avulsion and its management among dental assistants in Riyadh, Saudi Arabia and to assess its relationship with their educational background.MethodsA convenience sampling methodology was employed for sample selection. Over a period of four months starting in February, 2013, 691 pretested 17-item questionnaires were distributed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(65 citation statements)
references
References 19 publications
1
63
0
1
Order By: Relevance
“…The restoration of a fractured tooth must have a satisfactory level in relation to aesthetics, because even in cases of simple fractures, there is need for appropriate follow-up, since the prognosis of crown fractures depends not only on an accurate diagnosis, but also on appropriate restorative procedures [30]. The treatment of traumatic dental injuries is an important health promotion strategy that can significantly prevent negative biological and social impacts [19,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The restoration of a fractured tooth must have a satisfactory level in relation to aesthetics, because even in cases of simple fractures, there is need for appropriate follow-up, since the prognosis of crown fractures depends not only on an accurate diagnosis, but also on appropriate restorative procedures [30]. The treatment of traumatic dental injuries is an important health promotion strategy that can significantly prevent negative biological and social impacts [19,33].…”
Section: Discussionmentioning
confidence: 99%
“…W hereas a favorable prognosis for av ulsed / replanted depends significantly on the triad time the tooth remained outside the mouth, storage and appropriate transport medium, and minimal aggression to the root surface, knowledge of the emergency care of traumatic injuries is essential for tooth reestablishment and permanence in the mouth [19,29,32,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In regard to the education, the great majority of the participants in the present study were with university level and this fact affect the generation of relatively specific findings. It was found that educational qualifications and preceding advice or education about tooth avulsion were positively correlated with the level of knowledge about tooth avulsion and its management [19]. However, a number of studies have been published during the recent years showing insufficiency of care of traumatic dental injuries which might be due to insufficient knowledge on how to manage dental trauma on community base.…”
Section: Discussionmentioning
confidence: 99%